2020
DOI: 10.1080/23303131.2020.1797969
|View full text |Cite
|
Sign up to set email alerts
|

Representation through Lived Experience: Expanding Representative Bureaucracy Theory

Abstract: This study draws on the insights of managers in the behavioral health treatment system to explore the value of persons who bring lived experience to their organizational positions. Within these organizations, persons with relevant lived experience occupy various nonclinical and clinical positions. When facilities incorporate workers with lived experience, managers observe increased levels of trust between clients and service providers, an enhanced client-centered perspective among service providers, and higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 104 publications
0
12
0
1
Order By: Relevance
“…Nineteen of the 29 studies were qualitative and reported on outcomes from the perspectives of service users (Bocking et al, 2018 ; Fallin-Bennett et al, 2020 ; Gidugu et al, 2015 ; Taylor et al, 2018 ), mental health professionals (Agrawal et al, 2016 ; Collins et al, 2016 ; White et al, 2017 ), managers (Byrne et al, 2018 ; Merritt et al, 2020 ), caregivers (Yuen et al, 2019 ), and peer workers themselves (Griffiths & Hancock-Johnson, 2017 ). Several studies combined perspectives from some of the involved actors, either as part of case studies (Collins et al, 2019 ; Davies et al, 2014 ) or through interviews with several stakeholders (Barr et al, 2020 ; Brasier et al, 2022 ; Jack et al, 2018 ; Otte et al, 2019 ; Tseris, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nineteen of the 29 studies were qualitative and reported on outcomes from the perspectives of service users (Bocking et al, 2018 ; Fallin-Bennett et al, 2020 ; Gidugu et al, 2015 ; Taylor et al, 2018 ), mental health professionals (Agrawal et al, 2016 ; Collins et al, 2016 ; White et al, 2017 ), managers (Byrne et al, 2018 ; Merritt et al, 2020 ), caregivers (Yuen et al, 2019 ), and peer workers themselves (Griffiths & Hancock-Johnson, 2017 ). Several studies combined perspectives from some of the involved actors, either as part of case studies (Collins et al, 2019 ; Davies et al, 2014 ) or through interviews with several stakeholders (Barr et al, 2020 ; Brasier et al, 2022 ; Jack et al, 2018 ; Otte et al, 2019 ; Tseris, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The overall response was that the other participants highly valued peer workers’ involvement. Nevertheless, some studies revealed the fear that peer workers’ recovery process could negatively impact the support provided (Collins et al, 2016 , 2019 ; Ogundipe et al, 2019 ), that risks might arise as a result of peer workers’ lack of training and support (Griffiths & Hancock-Johnson, 2017 ; Merritt et al, 2020 ; Yuen et al, 2019 ), that boundaries between peer workers and service users are blurred (White et al, 2017 ), and that service users need to have opportunities to choose among peer workers as service providers (Ogundipe et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To advance theoretical development, research on symbolic representation would benefit from a deeper understanding of underlying mechanisms related to individual meanings and identities (Merritt et al, 2020; Ospina et al, 2018). The contextual factors that drive uncertainty and citizens' susceptibility to representation remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…«Verktøykassen» erfaringskonsulenter er i besittelse av som følge av sin liminale posisjon, kan gjøre dem i stand til å formidle erfaringer og kunnskap mellom ulike aktører, diskurser og kunnskapsformer. Erfaringskonsulenter beskrives videre ofte å ha et nettverk og en sosial kapital som hjelper dem å engasjere forskjellige aktører til å utvikle et sterkt engasjement (Bocking et al, 2018;Chisholm & Petrakis, 2020;Merritt et al, 2020). Det er også vanlig at erfaringskonsulenter har en sterk tilknytning til brukerorganisasjoner (Gillard et al, 2015;Åkerblom et al, 2020).…”
Section: Erfaringskonsulenter Befinner Seg I En «Liminal Posisjon»unclassified